2016
DOI: 10.11648/j.ajpn.20160403.11
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Alcohol Use Disorder and Depression Among Patients Attending a Tertiary Hospital in the Niger Delta Region of Nigeria

Abstract: Abstract:The study aims to ascertain the co-morbidity of Alcohol and Depression among patients attending the general outpatient clinic of the University of Port Harcourt Teaching Hospital. Via a system sampling method; 470 consenting subjects were enlisted in the study. The Alcohol Use Disorders Identification Inventory (AUDIT) and the Beck's Depression Inventory (BDI) were administered to each. Only one hundred and eighty five subjects met the criteria for the second stage of the study, (a score of 18 and abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our finding that the co-occurrence prevalence of depressive symptoms was 48.9% in AD patients closely corresponds with the findings of hospital-based studies conducted in other countries. For example, Ugochukwu et al reported that the prevalence of major depression among 470 patients with alcohol use disorder was 45.8% in a tertiary hospital in Nigeria (6). Another study conducted by Odlaug and colleagues showed that the rate of depression among 2,979 AD patients was 43.1% in eight European countries (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding that the co-occurrence prevalence of depressive symptoms was 48.9% in AD patients closely corresponds with the findings of hospital-based studies conducted in other countries. For example, Ugochukwu et al reported that the prevalence of major depression among 470 patients with alcohol use disorder was 45.8% in a tertiary hospital in Nigeria (6). Another study conducted by Odlaug and colleagues showed that the rate of depression among 2,979 AD patients was 43.1% in eight European countries (7).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of their co-occurrence in individuals with AD fluctuates markedly, according to how depressive symptoms are measured or defined. Epidemiologic data showed that the comorbidity rate in the general population varied between 15% and 28% (1,(3)(4)(5), whereas in clinical samples, this rate was much higher, ranging from 43% to 48% (6,7). Moreover, AD is significantly associated with depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation